Experimental Study on Effect of Addition of Different Salts on Distribution of Aniline between Water and Toluene - Wagh, Shrikant J.; Raulji, Shaktisingh G.; Gaddam, Sathish (Asian Journal of Engineering and Applied Technology, 2021)
The aim of this experimental work was to know the effect of addition of certain inorganic salts on removal of aniline from water by using toluene as the extracting solvent. The inorganic salts used were NaCl, KI, and MgCl2·6H2O. The influence of factors such as amount of salt, phase volume ratio, initial aniline concentration in feed-water solution, and temperature on the distribution of aniline was investigated. It was found that addition of 5% NaCl shows an appreciable salting-out effect on distribution of aniline. It was also found that the distribution of aniline was favoured at low aniline concentrations, and a phase volume ratio of toluene to water of little above 1.0. It is also found that the dissociation of salt added plays an important role in aniline extraction and the effect of cation and/or anion as predicted by the Hofmeister series may not be always followed in all cases. The distribution of aniline between water and toluene is found to be endothermic in nature.